2022
DOI: 10.1007/s11033-022-07540-9
|View full text |Cite
|
Sign up to set email alerts
|

α-Enolase inhibits apoptosis and promotes cell invasion and proliferation of skin cutaneous melanoma

Abstract: Background The glycolytic enzyme, α-Enolase (ENO1), catalyzes the production of phosphoenolpyruvate from 2-phosphoglycerate, thereby enhancing glycolysis and contributing to tumor progression. In the present study, we aimed to determine the role of ENO1 in skin cutaneous melanoma (SKCM) and the potential underlying mechanism. Methods The Sangerbox database was used to analyze the mRNA expression of ENO1 in SKCM. Western blotting was used to assess the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Recently, ENO1 was found to play important roles in regulating cell proliferation 46 , 47 , hypoxia induction and autoimmunity, in addition to its classical role as an enzyme in glycolysis 48 , 49 . Some studies have suggested that ENO1 can directly activate the PI3K/AKT signaling pathway to promote the proliferation of cancer cells 50 , including pancreatic cancer and gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ENO1 was found to play important roles in regulating cell proliferation 46 , 47 , hypoxia induction and autoimmunity, in addition to its classical role as an enzyme in glycolysis 48 , 49 . Some studies have suggested that ENO1 can directly activate the PI3K/AKT signaling pathway to promote the proliferation of cancer cells 50 , including pancreatic cancer and gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study have shown that ENO1 overexpression promoted proliferation, invasion and migration of SKCM cells; and increased pyruvate and lactate production (24). Subsequently, we explored the hypothesis that ENO1 is one of the leading regulators of the Warburg effect and thus plays a major role in carcinogenesis and tumor maintenance.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 Specifically, TRPM1, enolase, and aldolase have been closely associated with melanoma. 19 , 20 , 21 Funduscopic changes of AIR are characteristically unremarkable at presentation but have been documented to change over time and include vascular attenuation, diffuse chorioretinal atrophy, and retinal pigment epithelium mottling. 22 Full-field ERG of our patient demonstrated attenuated a- and b-waves more consistent with CAR and cases of non-paraneoplastic AIR rather than MAR which classically exhibit electronegative b-waves.…”
Section: Discussionmentioning
confidence: 99%